Gender differences in utilization of preventive care services in the United States - Vaidya, Varun; Partha, Gautam; Karmakar, Monita (Journal of women's health (Larchmont, N.Y. 2002), 2012)
The utilization of preventive care services in the United States remains low, despite health-care costs being as high as $2.3 trillion. While gender disparities have been known to exist for utilization of overall health-care services, the same issue has not been probed for preventive care utilization. A retrospective, cross-sectional study using the 2008 Medical Expenditure Panel Survey (MEPS). Preventive care services common to both genders were included (blood pressure checkup, cholesterol checkup, sigmoidoscopy/colonoscopy, flu shot, and dental checkup). Guideline adherence was determined using clinically accepted guidelines such as Joint National Committee 7 and the American Cancer Society. Descriptive statistics were used to describe the population, and chi-square analysis was used to determine the within group differences between the two genders. A multivariate logistic regression was built to determine the likelihood of guideline adherence based on gender while adjusting for known demographic confounders such as age, race, and ethnicity. There were 33,066 MEPS respondents for 2008. Of these, 4,291 to 30,629 met the inclusion criteria depending on the specific preventive care service being analyzed. Men were found to have significantly lower odds of using blood pressure check (odds ratio [OR] 0.35, 95% confidence interval [CI] 0.32-0.38), cholesterol check (OR 0.64, CI 0.60-0.69), dental check (OR 0.71, CI 0.68-0.75), and flu shots (OR 0.71, CI 0.67-0.76). While men had lower utilization for sigmoidoscopy/colonoscopy, the difference was nonsignificant. Preventive care utilization was found to be higher in women than in men. The gender disparity issue needs to be explored in greater detail to understand these differences.